Pengembangan Teknologi IoT Melalui Metode Demonstrasi dan Ekperimen Bagi Siswa SMA X di Kota Bandung - Audyati Gany (LPPM Universitas Yudharta Pasuruan, 2020)
Community service is one of the Tri Dharma Colleges that must be carried out by higher education institutions no exception for Maranatha Christian University. Community-based devotional activities provide additional knowledge of Internet of Things (IoT) technology to high school students of class 12 science SMA X Bandung. The topic of community service activities this time is in accordance with the agreement of cooperation between the SMA X Bandung and the Electrical Engineering Study Program of Maranatha Christian University which coincided with the initial debriefing activity of the new academic year, namely by providing knowledge of IoT technology and its application to students of SMA X Bandung so that students can know and understand the development of IoT technology that is growing rapidly at this time. The material provided in community service activities is the introduction of IoT, the basic electronic components, the introduction of Arduino, the application of IoT, and the Blynk application for IoT. The training methods used are tutorials and practices, with 70% of the practice in the demonstration and experimental methods. Participants in this activity gain knowledge and understanding of IoT technology, can realize a simple IoT application, and can realize IoT using the Blynk application on a smartphone.